AB0282 SYSTEMATIC REVIEW OF STUDIES REPORTING ON COGNITIVE FUNCTION IN RHEUMATOID ARTHRITISCOMPARED TO THE GENERAL POPULATION. (June 2019) - Szlachetka, Teresa; Linda, LI; Liu-Ambrose, Teresa; Xie, Hui; Yazdani, Kiana; Lacaille, Diane
Abstract : Background: Rheumatoid arthritis (RA) patients often complain of "brain fog" as a symptom when their disease activity is greater. The exact areas of cognition that this "brain fog" means are not yet understood. Previous studies have found that people with RA have lower cognitive function (CF) than healthy controls and age based population norms. A study by Shin et al which looked at prevalence of cognitive impairment in persons with RA found that 31% of their 115 person sample was cognitively impaired and stated that further studies should be done to identify the specific domains of cognitive function that are most commonly affected (1). In this project, I will be looking at and summarizing all the data and findings that have been collected and reported on CF in the RA population and seeing which domains of cognition differ and which do not differ when compared to the general population and aged based population norms. Objectives: To conduct a systematic review of studies reporting on cognitive function (CF) in rheumatoid arthritis (RA) patients compared to non-RA populations (based on comparison with a control group or age-based population norms). Methods: We conducted a comprehensive literature search of MEDLINE, EMBASE, and PUBMED databases using the following search terms: rheumatoid arthritis or arthritis or inflammatory arthritis, and cognitive function or cognition. The search was conducted with no limit for years, and confined to only articles in English or French. After title and abstract screen, relevant articles were selected for review. Only full length articles were considered. Study selection criteria included: 1) must be presenting original data, 2) must contain RA group with confirmed diagnosis, 3) must be reporting on CF in RA, 4) must use a validated measure of CF (self-reported or from conducting CF tests), and 5) must contain a healthy control group or age-based populations norms. Selected articles were critically appraised using the SIGN Methodology Checklist and data extracted using a standardized form. Results: Our initial literature search yielded 747 titles, and after screening for irrelevant titles and duplicates, 28 abstracts remained. Upon excluding non-full length articles and articles which did not report on CF, 13 abstracts remained. Of these 13 articles, 8 met our selection criteria. All studies were published after the year 2000, 3 were from the USA, 1 from Canada, 1 from the UK, 1 from Australia, 1 from Egypt, and 1 from Taiwan. Sample sizes for RA and control groups varied from 15 to 120. Of these 8 articles, 6 found a significant difference in cognitive function in the RA group compared to control group or age-based population norms in at least one domain of CF. All articles that found a significant difference in CF used standardized neuropsychological tests. Domains of CF that differed included fluency, attention, visual-spatial learning, memory, decision making time, and simple reaction time. Domains of CF that were not found to differ from general population across all studies included reasoning, comprehension, and intelligence (IQ). Conclusion: Overall, 75% of the articles reviewed found a significant difference in at least one domain of CF in RA patients compared to healthy controls or age-based population norms. The domains of CF most commonly affected are those related to processing and speed rather than intellectual ability. Further studies are needed to explore these differences in greater depth and to understand the underlying reasons for these differences. Reference: [1] Shin, So Young, Patricia Katz, Margaret Wallhagen, and Laura Julian. 2012. "Cognitive Impairment in Persons with Rheumatoid Arthritis."Arthritis Care & Research. Disclosure of Interests: Teresa Szlachetka: None declared, Linda Li: None declared, Teresa Liu-Ambrose: None declared, Hui Xie: None declared, Kiana Yazdani: None declared, Diane Lacaille Grant/research support from: Bristol-Myers Squibb and Eli Lilly Canada